Variable structure control of manipulators with compliant joints - Tenreiro Machado, J. A. (1993)
This article studies the variable structure control of robot manipulators with flexible joints. A second order preference model and a smooth control law eliminate the reaching phase problems and the chattering usually present in the sliding mode. The results show a remarkable improvement of the stability over conventional variable structure controllers, while the algorithm maintains a low computational load that makes it well suited for microcomputer implementation.